Challenges in a Commodity Offering - Indian Telecom Services (GSM) - Subakaran, P. (Indian Journal of Marketing, 2012)
This paper is a theoretical research on the effect of branding in the Indian Telecom Services (GSM). Currently, number portability, dropping average revenue per user and a market approaching saturation presents challenges for cellular service providers. One of the fundamentals in branding is that a strong brand should give certain pricing power to its parent company. This is not observed in the telecom industry as average revenue per user is consistently declining. This paper highlights that the telecom service is becoming a commodity from the consumers' point of view. The only differentiation that may be experienced is the network availability and quality of coverage. Telecom service being a low involvement product with minimal differentiation; consumers would follow a learn-do-feel sequence in terms of their responses towards a telecom service brand. The quality of experience that the consumer has with the chosen telecom service provider is what is going to retain the consumer. Indian telecom service providers' focus would need to move from Customer Acquisition Numbers to Customer Lifetime Value. Service providers simply cannot afford to lose high-value subscribers. This is even more important in a 3G scenario, where data is expected to help boost revenues, and the attempt is to get more voice users to access data or other revenue generating applications on their phones.